EACR-MRS conference on seed and soil: in vivo models of metastasis - Alves, Inês; Kyjacova, Lenka; Sleeman, Jonathan P. (Clinical & experimental metastasis, 2018)
New experimental tools are urgently required to better understand the metastatic process. The importance of such tools is underscored by the fact that many anti-cancer therapies are generally ineffective against established metastases. This makes a major contribution to the fact that metastatic spread is responsible for over 90% of cancer patient deaths. It was therefore timely that the recent “Seed and Soil: In Vivo Models of Metastasis” conference held in Berlin, Germany (27-29 of November 2017) aimed to give an in-depth overview of the latest research models and tools for studying metastasis, and to showcase recent findings from world-leading metastasis researchers. This Meeting Report summarises the major themes of this ground-breaking conference.